EFFECT OF ARBUSCULAR MYCORRHIZAL COLONIZATION ON EARLY GROWTH AND NUTRIENT CONTENT OF TWO PEAT SWAMP FOREST TREE SPECIES SEEDLINGS, Calophyllum hosei AND Ploiarium alternifolium - Maman Turjaman; Erdy Santoso; Yutaka Tamai; Mitsuru Osaki; Keitaro Tawaraya (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2006)
Tropical peat-swamp forests are one of the largest near-surface reserves of terrestrial organic carbon, but rnany peat-swamp forest tree species decreased due over-exploitation, forest fire and conversion of natural forests into agricultural lands. Among those species are slow-growing Calophyllum hoseiand Ploiarium alternifolium, two species are good for construction of boats, furniture, house building and considerable attention from pharmacological viewpoint for human healthly. This study was aimed at understanding the effects of arbuscular mycorrhizal (AM) fungi on early growth of C. hosei and P.alternifoliumunder greenhouse condition. Seedlings of C. hosei and P.alternifoliumwere inoculated with AM fungi: Glomus clarum and Glomus aggregatum ,or uninoculated under greenhouse condition during 6 months. AM colonization, plant growth, survival rate and nutrient content (P, Zn and B) were measured. The percentage of C. hoseiand P.alternifolium ranged from 27-32% and 18-19%, respectively. Both inoculated seedling species had greater plant height, diameter, leaf number, shoot and root dry weight than control seedlings. Nutrient content of inoculated plants were increased with AM colonization- Survival rates of inoculated plants were higher (100%) than those of control plants (67%). The results suggested that inoculation of AM fungi could improve the early growth of C. hoseiand P.alternifolium grown in tropical peat-swamp forest therefore this finding has greater potential impact if this innovative technology applied in field scales which are socially acceptable, commercially profitable and environmentally friendly.